STRATEGI KOMUNIKASI RADIO EL JOHN 102.6 FM PEKANBARU DALAM MEMPERTAHANKAN PENGIKLAN - Fuady, Armi; Rimayanti, Nita (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Radio El John 102.6 FM is one of the senior radio that has long aired in Pekanbaru, in the face of the development of radio age El John 102.6 FM has its own strategy in maintaining its existence in the midst of an increasingly sophisticated media development. Advertisers are the largest source of revenue from a radio company, for it to establish good relationships with the clients of advertisers is something that must be done by radio El John 102.6 FM in an effort to realize its communication strategy. This study aims to determine the strategy of selecting communicators, knowing the message processing strategy, knowing the media selection strategy, and knowing the strategy in determining the target of radio communication El John 102.6 M Pekanbaru in maintaining the advertiser.This research was conducted in Radio El John 102.6 FM which is located at Jl. Soekarno Hatta Pekanbaru, SKA MAL Blok H 102. Research subjects are determined based on purposive techniques consisting of Marketing, General Manager, and Radio Producer. Data collection techniques include observation, interviews, and documentation.The results show that the communication strategy of El John 102.6 FM Pekanbaru radio in maintaining advertisers by establishing personal relationships with advertiser clients. The strategy used by El Jhon radio 102.6 FM is first by determining the communicator, who is appointed as a communicator is Marketing, General Manager, Radio Producer who has credibility in interacting with clients. Secondly with a messaging plan that includes both informative and persuasive messages, the third with media such as print and internet, the fourth with a communication audience is an advertiser client that has been working more than 3 months or so-called contract clients.